The Pashtun Family System in Mardan in the Light of the Seerah: An Analytical Study - Ayesha Karim (Journal of Religion and Society, 2025)
The Pashtun society is based on an ancient and traditional family structure rooted in Pashto customs, tribal principles, and historical continuity. This system is centered around patriarchal leadership, where the head of the family is a male, and all major decisions are made through the consultation and approval of elders. Institutions like the "Jirga" reflect the collective thinking of this system, whereas women are often deprived of decision-making, education, and inheritance rights. While the system upholds positive values such as unity, honor, respect for elders, and hospitality, it also includes several non-Islamic elements that need reform. This research paper presents an analytical study of the Pashtun family system in the specific context of District Mardan, viewed through the lens of the Seerah of Prophet Muhammad ﷺ. The paper presents a comparative analysis between the Seerah-based family values and the existing Pashtun system. It reveals that while values such as family unity, respect for elders, and consultation align with Islamic teachings, issues like limited roles for women, forced marriages, denial of inheritance, and male dominance contradict core Islamic principles. The presence of these un-Islamic practices not only disturbs social balance but also undermines the just family model of Islam. The goal of this research is not mere criticism, but to pave the way for constructive reform. It emphasizes the joint role of religious scholars, educational institutions, and tribal elders in bringing improvement. Inclusion of women's voices in the Jirga system, enforcement of inheritance laws, and Seerah-based training for the youth are essential steps. Only then can a family system be formed that respects cultural traditions while embodying Islamic values in practice. Keywords: Pashtun, Family System, Seerah of the Prophet ﷺ, Justice, Women, Tribal Traditions, Consultation, Reform